Analisis Cemaran DNA Tikus pada Bakso Daging Sapi yang Beredar di Makassar dengan Metode Polymerase Chain Reaction (PCR): Analysis of Rat DNA Contamination on Beef Meatballs Circulating in Makassar by Polymerase Chain Reaction (PCR) Method - Aminah, Aminah; Ramadini, Ristieyen; Naid, Tadjuddin (Universitas Tadulako, 2019)
Analysis of rat DNA contamination in meatball meat circulating in Makassar by PCR (Polymerase Chain Reaction) method has been carried out. In this study, a polymerase chain reaction method will be developed to analyze the presence of rat meat contamination in beef meatballs. There are three stages in the PCR amplification process carried out with 30 cycles, which are 95oC temperature denaturation, 51oC attachment, and 72oC extension. DNA analysis included agarose gel electrophoresis, measurement of concentration and purification, and analysis of rat DNA using PCR. The results of PCR amplification using mouse-specific primers namely primary ND1 (NADH dehydrogenase 1) showed no bands seen in UV light. So that it can be proven that beef meatball samples in the Makassar region did not contain rat DNA. t.